(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of the present study was to evaluate Urine Albumin-Creatinine Ratio (UACR) for albuminuria in patients with sepsis admitted to Medicine Intensive Care Unit (MICU) and its Correlation with SOFA score. Methods: The present study was conducted in the Department of General Medicine, Dr. D. Y. Patil Medical College, Hospital and Research Centre, Pimpri, Pune from August 2018 to September 2020. 40 patients were included in the present study. Results: The result shows the distribution of cases according to age. It was observed that the maximum number of subjects with sepsis (45%) was in 18 – 40 years age group. 22.5% of patients belonged to the above 60 age group. Mean age of the study subjects was 44.45 ± 18.43 years. Majority of the patients admitted due to sepsis were male 24 (60%) and 16 patients (40%) were female. In our study, abnormal hemoglobin levels (<12.3) were found in 35 (87.5%) out of 40 patients with a mean of 10.22 ±2.16. Out of 40 patients 26 (65%) were found to have elevated CRP levels and mean CRP was 79.2975. Liver function tests revealed that out of 40 patients 20 had elevated total bilirubin levels with mean of 4.40 ±8.49. Conclusion: In this study several possibilities for the future application of UACR in critically ill patients were highlighted. For early detection of patients with sepsis needing early targeted therapy, routine UACR surveillance could potentially help. Microalbuminuria, a non-invasive and easily available bed side investigation, can be used as a marker for prediction of mortality and morbidity.